A nickel-zinc soft ferrite and preparation method thereof

By adjusting the ratio of each component in the ferrite and adding a layered structure dispersion carrier and modification additive, the problem of poor dispersion of components in the nano nickel-zinc soft magnet ferrite powder is solved, and the uniformity and stability of the electromagnetic properties of the nickel-zinc soft magnet ferrite is improved.

CN114388210BActive Publication Date: 2025-03-04SHENZHEN MELASTA BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210075268.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-22
Publication Date
2025-03-04
Estimated Expiration
2042-01-22

AI Technical Summary

Technical Problem

The dispersion between the components in the nano nickel-zinc soft ferrite powder is poor, resulting in poor strength uniformity of the nickel-zinc soft ferrite obtained by pressing, which leads to poor electromagnetic performance stability.

Method used

By adjusting the ratio of each component in the ferrite, the content of the zinc source is increased, and the layered dispersion carrier, such as mordenite, and modification additives such as graphite, polyaniline and polyacrylamide, a conductive network structure is constructed to enhance the load and dispersion effect of the dispersion carrier on the ferrite powder.

Benefits of technology

The uniformity and stability of the electromagnetic properties of nickel-zinc soft magnet ferrite are improved, and the possibility of agglomeration between ferrite powders is reduced, so that the thinner ferrite material can maintain relatively uniform electromagnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
  • Figure DEST_PATH_IMAGE003
    Figure DEST_PATH_IMAGE003
  • Figure DEST_PATH_IMAGE005
    Figure DEST_PATH_IMAGE005
Patent Text Reader

Abstract

The present application relates to the field of magnetic conductive materials, and specifically discloses a nickel-zinc soft magnetic ferrite and a preparation method thereof. A nickel-zinc soft magnetic ferrite comprises the following materials in parts by weight: 25-35 parts of an iron source, 3.5-9.5 parts of a nickel source, 4-10 parts of a zinc source, 10-20 parts of ammonia monohydrate, 20-30 parts of water, 1-2 parts of an additive and 2-3 parts of a dispersant, wherein the dispersant comprises a dispersion carrier of a layered structure, and the dispersion carrier comprises mordenite. The preparation method thereof is as follows: S1, mixing raw materials; S2, preparing a soft magnetic ferrite. The nickel-zinc soft magnetic ferrite of the present application can be used in the fields of transformers, electronic components, etc., and has the effect of uniform magnetic conductivity and electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of magnetic conductive materials, and in particular to a nickel-zinc soft magnetic ferrite and a preparation method thereof. Background Art

[0002] Soft ferrite materials are inorganic non-metallic magnetic materials made by mixing compounds (oxides) of metal elements such as iron, nickel, manganese, zinc, and magnesium in a certain proportion, and then undergoing ball milling, firing, pressing, and other steps. Compared with general metals, soft magnetic ferrite materials have the advantages of good magnetic conductivity, weak coercivity, small remanence after the external current is removed, and low medium and high frequency losses. Due to its better magnetic conductivity, it is widely used in filters, load coils, transformers, sensors and other fields. Soft ferrites can be divided into four types according to their different formulas: manganese-zinc ferrites, nickel-zinc ferrites, barium-zinc ferrites, and magnesium-zinc ferrites.

[0003] Due to the characteristics of high frequency, wide frequency, high impedance and low loss, nickel-zinc ferrite has been paid more and more attention in recent years and has become a soft ferrite material with wide application and excellent performance in the high frequency range. According to the field of use, nickel-zinc ferrite can be divided into: high magnetic permeability nickel-zinc ferrite, power nickel-zinc ferrite and anti-electromagnetic interference nickel-zinc ferrite. Among them, high-power nickel-zinc ferrite is also called power supply ferrite, which is mainly used in pulse magnetic field transformers and other fields. With the changes in the market, the size of various electronic products is shrinking, which in turn requires the size of electronic components to be reduced.

[0004] With regard to the above-mentioned related technologies, the inventors believe that after electronic components are made smaller and thinner, it is usually necessary to use nano nickel zinc soft ferrite powder to make the components. Due to the poor dispersibility between the components in the nano nickel zinc soft ferrite powder, the strength uniformity of the pressed nickel zinc soft ferrite is poor, which in turn leads to the defect of poor stability of electromagnetic properties of the nickel zinc soft ferrite. Summary of the invention

[0005] In order to improve the defect of poor stability of magnetic induction performance of nickel-zinc soft ferrite, the present application provides a nickel-zinc soft ferrite and a preparation method thereof.

[0006] In the first aspect, the present application provides a nickel-zinc soft ferrite, which adopts the following technical solution:

[0007] A nickel-zinc soft magnetic ferrite comprises the following materials in parts by weight: 25-35 parts of an iron source, 3.5-9.5 parts of a nickel source, 4-10 parts of a zinc source, 10-20 parts of monohydrated ammonia, 20-30 parts of water, 1-2 parts of an additive and 2-3 parts of a dispersant, wherein the dispersant comprises a dispersing carrier with a layered structure, and the dispersing carrier comprises mordenite.

[0008] By adopting the above technical solution, first, the ratio of each component in the ferrite is adjusted to increase the content of the zinc source in the ferrite. During the sintering process, the zinc atoms enter the ferrite lattice, which changes the mass transport process during the crystal growth process and increases the growth rate of the grains. After the grain growth rate increases, the lattice expands, the powder is more active, and it is beneficial to improve the size of the grains. However, the size of the grains is still nanometer-level, which is beneficial to reduce the possibility of agglomeration between the various components of the ferrite, and then the ferrite products can maintain relatively uniform electromagnetic properties after being thinned.

[0009] Secondly, adding a layered dispersed carrier to the ferrite can separate the ferrite powder to a certain extent by loading the ferrite powder, reduce the possibility of ferrite powder agglomeration, and improve the uniformity of the electromagnetic properties of ferrite products.

[0010] Finally, mordenite is added to the ferrite. The mordenite has an interlaced skeleton structure, and the pores formed are small in diameter, which can selectively adsorb nanomaterials. At the same time, mordenite also has a better electrostatic effect, which can not only further adsorb the ferrite material, but also improve the electromagnetic properties of the ferrite material and further reduce the possibility of agglomeration of the ferrite material. In addition, mordenite further catalyzes the reaction between the components in the ferrite material, and stably improves the electromagnetic properties of the ferrite material.

[0011] Preferably, the dispersed carrier further comprises any one of nano spinel and mesoporous silica, and the mass ratio of mordenite: nano spinel: mesoporous silica is 2-3:1-2:1-2.

[0012] By adopting the above technical solution, mordenite and nano spinel are used as dispersion carriers in combination, and nano spinel can play a bonding role under the catalytic effect of mordenite. After mordenite and nano spinel are combined with each other, the bonding effect between the dispersion carrier and the ferrite powder is improved, and the possibility of agglomeration between the ferrite powders is further reduced, so that the ferrite obtains more uniform electromagnetic properties. At the same time, the nano spinel can also induce the ferrite powder to form a spinel structure, thereby improving the electromagnetic properties of the ferrite.

[0013] Secondly, the technical solution of the present application adopts mordenite and mesoporous silica in combination as a dispersion carrier. Mesoporous silica has a three-dimensional pore structure. The morphology of the pore channels in the dispersion carrier is increased by the combination of mordenite and mesoporous silica, so that ferrite powders of different particle sizes can be adsorbed and encapsulated by the dispersion carrier, further improving the dispersion uniformity between the components in the ferrite.

[0014] Preferably, the dispersion carrier is a dispersion carrier modified by a modification agent, the modification agent includes polyaniline, graphite and polyacrylamide, and the mass ratio of the polyaniline, graphite and polyacrylamide is 1-2:1-2:1-3.

[0015] By adopting the above technical scheme, the dispersion carrier is modified by using polyaniline, graphite and polyacrylamide. Since graphite has a relatively fluffy mesh structure, a conductive mesh structure can be constructed on the dispersion carrier, which not only enhances the adsorption and packaging effect of the dispersion carrier on the ferrite material, but also enhances the bonding performance between the modified additive and the dispersion carrier.

[0016] The gel network structure of polyacrylamide can stably improve the bonding effect between the components in the modification aid, so that the modification aid can stably modify the dispersion aid. Finally, polyaniline can coat the inner wall of the pores of the dispersion carrier, so that a polyaniline film structure is formed on the dispersion carrier, which increases the conductive effect of the dispersion carrier, enhances the toughness of the ferrite material, and further improves the electromagnetic properties of the thinned ferrite material. Therefore, after polyaniline, graphite and polyacrylamide cooperate with each other, a stable conductive structure can be formed, and a coating film structure can be formed on the inner wall of the pores of the dispersion carrier, which enhances the bonding effect between the dispersion carrier and the ferrite powder, and improves the toughness of the ferrite, which is conducive to the thinning of ferrite products.

[0017] Preferably, the modification treatment includes the following steps: respectively weighing 6-8 parts of a dispersion carrier, 2-5 parts of sodium hydroxide, 20-30 parts of water, 10-15 parts of hexadecyltrimethylammonium bromide and 1-3 parts of a modification aid; stirring and mixing the dispersion carrier and sodium hydroxide, calcining to obtain a mixture, stirring and mixing the mixture with water, leaching, and taking the upper layer liquid as the leachate; stirring and mixing the leachate, hexadecyltrimethylammonium bromide and the modification aid, and continuously stirring to obtain a mixed solution; taking the mixed solution for crystallization reaction, and calcining to obtain a dispersion carrier modified with the modification aid.

[0018] By adopting the above technical scheme, sodium hydroxide is added in the modification process, the dispersion carrier is alkali-etched, the ash and impurities blocking the pores of the dispersion carrier are eliminated, and the pores on the dispersion carrier are expanded to increase the specific surface area and surface porosity of the dispersion carrier. Hexadecyltrimethylammonium bromide is then added as a template in the modification process. The hydrophilic group and hydrophobic group of hexadecyltrimethylammonium bromide will form an ordered micelle structure, guide the dispersion carrier to undergo a regular crystallization reaction, and self-assemble to form an ordered hexagonal aperture structure, so that the pores on the dispersion carrier are evenly distributed, and the encapsulated ferrite powder is carried more evenly.

[0019] Preferably, the concentration of hexadecyltrimethylammonium bromide in the modification treatment is 3-5 g / L, the pH of the mixed solution is adjusted to 10-11, the crystallization temperature in the crystallization reaction is 90-110° C., and the crystallization time is 50-70 h.

[0020] By adopting the above technical scheme, adjusting the concentration of hexadecyltrimethylammonium bromide and the pH of the mixed solution, adjusting the concentration of micelles and hexagonal liquid crystal phases in the reaction solution, and inhibiting the polycondensation between the silicon-aluminum structure in the dispersed carrier, it is beneficial to improve the distribution uniformity of the pores on the dispersed carrier. At the same time, the present application selects a suitable crystallization temperature, optimizes the crystallization time, accelerates the nucleation rate of the dispersed carrier, shortens the induction period and increases the crystallization rate. The formed pore structure is stable and not prone to collapse, so that the pore structure on the dispersed carrier can be more stably loaded with ferrite powder, reducing the possibility of agglomeration between the various components of ferrite.

[0021] Preferably, after the modification treatment, the dispersion carrier modified by the modification aid is mixed with a binding aid, wherein the binding aid comprises silica gel and epoxy resin in a mass ratio of 3-5:1-2.

[0022] By adopting the above technical solution, the silica gel has a three-dimensional network structure, and the epoxy resin has better adhesive properties. Therefore, after the modification treatment, the binding aid is mixed with the dispersion carrier, and the binding aid can be loaded on the inner wall of the pores of the dispersion carrier to form a membrane structure. On the one hand, the three-dimensional network structure in the binding aid stably supports the pores on the dispersion carrier, reducing the possibility of collapse of the pores of the dispersion carrier; on the other hand, the membrane structure formed by the binding aid has a better bonding effect, enhances the encapsulation effect of the dispersion carrier on the ferrite powder, and stably reduces the possibility of agglomeration between the various components of the ferrite.

[0023] Preferably, the dispersant further comprises a dispersing aid, and the dispersing aid comprises any one of polyvinyl alcohol, zinc stearate and triethanolamine.

[0024] By adopting the above technical scheme, polyvinyl alcohol can not only act as a binder to improve the binding effect between ferrite powder and dispersion carrier, but also act as a surfactant to improve the dispersion effect between various components in ferrite materials. Zinc stearate has a good lubricating effect, and after being matched with the dispersion carrier, it can not only reduce the possibility of agglomeration between the dispersion carriers, but also stably reduce the possibility of agglomeration between various components of ferrite, stably improve the strength uniformity of ferrite products, and improve the electromagnetic properties of ferrite. Triethanolamine is used as a surfactant. After triethanolamine is matched with the dispersion carrier, it can not only trim the formation of ferrite, so that the iron oxide forms a spherical structure, but also reduce the possibility of agglomeration between various components of ferrite.

[0025] Preferably, the additive includes one or more of niobium pentoxide, molybdenum oxide and tin oxide.

[0026] By adopting the above technical solution, niobium pentoxide is added to ferrite, which promotes the grain growth of ferrite and inhibits the discontinuous growth of grains. Therefore, the amount of pores in the ferrite grains can be reduced, the sintering density can be increased, and the power loss density of ferrite can be effectively reduced, that is, the electromagnetic properties of ferrite can be improved.

[0027] By using molybdenum oxide as an additive, molybdenum ions exist in the grain boundaries, thereby increasing the metal ion vacancies near the grain boundaries, accelerating the movement of the grain boundaries, promoting the increase of the grain size, thereby improving the magnetic permeability, and reducing the possibility of agglomeration of ferrite powders.

[0028] By using tin oxide as an additive, tin ions can be substituted in the crystal lattice without changing the spinel structure of the ferrite. At the same time, a liquid phase can be formed during the sintering process, thereby promoting the growth and densification of ferrite grains, obtaining a more uniform particle size distribution, and improving the electromagnetic properties of the ferrite.

[0029] Finally, niobium pentoxide, molybdenum oxide and tin oxide are used as additives in combination, and the ratio between the components in the additives is adjusted. On the one hand, the discontinuous growth of ferrite grains is inhibited, the grain size is increased, and the magnetic properties of ferrite are increased. On the other hand, the liquefaction of tin oxide during the sintering process not only improves the doping efficiency of the additive in ferrite, but also improves the density of ferrite grains, thereby stably improving the electromagnetic properties of ferrite.

[0030] In a second aspect, the present application provides a method for preparing a nickel-zinc soft ferrite, using the following technical solution:

[0031] A method for preparing a nickel-zinc soft ferrite comprises the following preparation steps: S1, raw material mixing: stirring and mixing an iron source, a zinc source and a nickel source to obtain a mixed material, stirring and mixing the mixed material, water, ammonia monohydrate, an additive and a dispersant, and continuously stirring to obtain an intermediate solution; S2, soft ferrite preparation: subjecting the intermediate solution to a crystallization reaction to obtain a crystallized product, and the crystallized product is filtered, a precipitate is retained, washed, dried, sintered and cooled to obtain ferrite.

[0032] By adopting the above technical scheme and the co-precipitation method to prepare ferrite, the ferrite can undergo a crystallization reaction again during the reaction process, which can not only adjust the morphology of the ferrite, but also enhance the loading of the ferrite powder on the dispersion carrier. As the loading of the ferrite powder on the dispersion carrier forms an adsorption and desorption equilibrium state, it is beneficial to enhance the dispersion effect between the various components of the ferrite and reduce the possibility of agglomeration between the various components of the ferrite.

[0033] Preferably, the sintering temperature in step S2 is 400-500°C.

[0034] By adopting the above technical scheme and using a suitable sintering temperature, not only the shape of the ferrite powder can be trimmed, but also the ferrite powder can be promoted to enter the dispersion carrier, so that the bonding performance between the ferrite powder and the dispersion carrier is enhanced, and the ferrite finally formed obtains a relatively complete grain morphology, which is beneficial to improving the strength uniformity of the ferrite, that is, improving the electromagnetic properties of the ferrite.

[0035] In summary, this application has the following beneficial effects:

[0036] 1. Since the present application uses the method of adjusting the ratio between the components in the ferrite, increasing the content of zinc atoms in the ferrite, accelerating the growth rate of the grains, and causing the lattice to expand, thereby increasing the size of the grains and reducing the possibility of agglomeration between the components of the ferrite, the ferrite product can still maintain relatively uniform electromagnetic properties after being thinned; due to the addition of a dispersed carrier with a layered structure, the ferrite powder is loaded on the dispersed carrier, and the ferrite powder that is easy to agglomerate can be separated, and the mordenite has a better conductive effect, which stably reduces the possibility of agglomeration of the ferrite powder, so that the ferrite obtains a relatively uniform electromagnetic property.

[0037] 2. In the present application, it is preferred to use a modification aid to modify the dispersion carrier. Due to the mutual cooperation of graphite, polyaniline and polyacrylamide, a conductive network structure can be constructed on the dispersion carrier, thereby enhancing the adsorption and encapsulation effect of the dispersion carrier on the ferrite powder, improving the toughness of the ferrite material, and reducing the possibility of ferrite powder agglomeration. Therefore, the ferrite obtains a more uniform and stable electromagnetic effect.

[0038] 3. The method of the present application prepares ferrite by a co-precipitation method, so that the ferrite can undergo multiple crystallization reactions. On the one hand, the shape of the ferrite can be regularized, and on the other hand, the bonding performance between the ferrite and the dispersed carrier is enhanced, and the possibility of agglomeration between the components of the ferrite is synergistically reduced. Therefore, the ferrite obtains a more uniform and stable electromagnetic performance effect. DETAILED DESCRIPTION

[0039] The present application is further described in detail below with reference to the embodiments.

[0040] In the embodiments of the present application, the instruments and equipment used are as follows, but not limited thereto:

[0041] Instruments: 105645 magnetometer from Shanghai Jinmao Industrial Technology Co., Ltd. and ZJD-B tester from Beijing Aerospace Zongheng Testing Instrument Co., Ltd.

[0042] Drugs: Nano-mordenite with a bulk density of 0.5g / mL produced by Zhuoran Environmental Technology (Dalian) Co., Ltd., mesoporous silica with a pore size of 3nm produced by Nanjing Jike Biotechnology Co., Ltd., zinc stearate with a particle size of 60μm produced by Shijiazhuang Zhuzhong Technology Co., Ltd., graphite with an expansion degree of 300 produced by Shijiazhuang Tourmaline Mineral Products Co., Ltd., and nano-aluminum-magnesium spinel produced by Gongyi Zhijun Refractory Co., Ltd.

[0043] Preparation Example

[0044] Additive Preparation Example

[0045] Preparation Example 1-5

[0046] Weigh niobium pentoxide, molybdenum oxide and tin oxide respectively, the specific masses are shown in Table 1, stir and mix to prepare additives 1-5

[0047] Table 1 Composition of additives in Preparation Examples 1-5

[0048]

[0049] Preparation Example 6

[0050] Nickel chloride was used as the nickel source.

[0051] Preparation Example 7

[0052] Zinc chloride was used as the zinc source.

[0053] Preparation Example 8

[0054] Ferric chloride was used as the iron source.

[0055] Dispersed carrier preparation example

[0056] Preparation Examples 9-13

[0057] Nanospinel, mesoporous silica and mordenite were weighed respectively, with specific masses shown in Table 2, and stirred and mixed to prepare dispersed carriers 1-5.

[0058] Table 2 Preparation Examples 9-13 Dispersed Carrier Composition

[0059]

[0060] Preparation example of modified additive

[0061] Preparation Examples 14-16

[0062] Weigh polyaniline, graphite and polyacrylamide respectively, the specific masses are shown in Table 3, stir and mix, and prepare modification additives 1-3.

[0063] Table 3 Composition of modified additives in Preparation Examples 14-16

[0064]

[0065] Preparation Examples 17-19

[0066] The difference from Preparation Example 11 is that the dispersion carrier is a dispersion carrier modified with a modification aid, and the dispersion carrier 3, sodium hydroxide, water, 3 g / L of hexadecyltrimethylammonium bromide and modification aid 1 are weighed respectively, and the specific masses are shown in Table 4. The dispersion carrier and sodium hydroxide are stirred and mixed to obtain a mixture, and the mixture is calcined at 600°C for 2h. The mixture is stirred and mixed with water, leached, and the upper layer liquid is taken as the leachate; the leachate, hexadecyltrimethylammonium bromide and the modification aid are stirred and mixed in a 35°C water bath, and stirring is continued to obtain a mixed solution, and the pH is adjusted to 10; the mixed solution is subjected to a crystallization reaction, the crystallization temperature is 90°C, the crystallization time is 50h, and it is calcined at 550°C for 6h to obtain a dispersion carrier 1-3 modified with a modification aid.

[0067] Table 4 Composition of the dispersed carrier modified by the modification agent in Preparation Examples 17-19

[0068]

[0069] Preparation Example 20-21

[0070] The difference from Preparation Example 18 is that modification aid 2-3 is used to replace modification aid 1 in Preparation Example 18 to prepare dispersion carrier 4-5 modified by modification aid.

[0071] Preparation Example 22

[0072] The difference from Preparation Example 18 is that the concentration of hexadecyltrimethylammonium bromide is 3.6 g / L, the pH of the mixed solution is adjusted to 10.5, the crystallization temperature in the crystallization reaction is 100°C, the crystallization time is 60 h, and the dispersed carrier 6 modified with a modification aid is prepared.

[0073] Preparation Example 23

[0074] The difference from Preparation Example 18 is that the concentration of hexadecyltrimethylammonium bromide is 5 g / L, the pH of the mixed solution is adjusted to 11, the crystallization temperature in the crystallization reaction is 110°C, the crystallization time is 70 h, and the dispersed carrier 7 modified with a modification aid is prepared.

[0075] Preparation example of bonding aid

[0076] Preparation Examples 24-26

[0077] Silica gel and epoxy resin were weighed separately, the specific masses were shown in Table 5, and stirred to obtain a binding agent 1-3. The binding agent was stirred and mixed with a dispersion carrier 6 modified with a modification agent, filtered, the solid matter was retained, and dried to obtain a dispersion carrier 1-3 with a binder added.

[0078] Table 5 Composition of the bonding aids in Preparation Examples 24-26

[0079]

[0080] Preparation example of dispersing aid

[0081] Preparation Example 27

[0082] 2 kg of polyvinyl alcohol was used as the dispersing aid 1.

[0083] Preparation Example 28

[0084] 2 kg of zinc stearate was used as dispersing aid 2.

[0085] Preparation Example 29

[0086] 2 kg of triethanolamine was used as the dispersing aid 3. Example

[0087] Examples 1-3

[0088] In a first aspect, the present application provides a nickel-zinc soft ferrite, comprising the following substances: an iron source, nickel, a zinc source, ammonia monohydrate, water, an additive and a dispersant, the specific masses of which are shown in Table 6, and the dispersant comprises a dispersion carrier 1.

[0089] In the second aspect, the present application provides a method for preparing a nickel-zinc soft ferrite, comprising mixing raw materials: stirring and mixing an iron source, a zinc source and a nickel source to obtain a mixed material, stirring and mixing the mixed material, water, ammonia monohydrate, an additive and a dispersant, ultrasonically dispersing for 1 hour, and continuously stirring in a 40°C water bath for 8 hours to obtain an intermediate solution, adjusting the pH to 110, and continuing stirring for 2 hours; transferring the intermediate solution into a reactor coated with polytetrafluoroethylene to carry out a crystallization reaction at 180°C for 8 hours to obtain a crystallized product, and filtering the crystallized product, retaining the precipitate, washing, drying, sintering at 400°C, and cooling to obtain ferrite 1-3.

[0090] Table 6 Ferrite composition of Example 1-3

[0091]

[0092] Embodiment 4-7

[0093] The difference from Example 2 is that the dispersant includes dispersion carriers 2-5 respectively, and ferrites 4-7 are obtained.

[0094] Embodiment 8-14

[0095] The difference from Example 2 is that the dispersants respectively include dispersion carriers 1-7 modified by a modification aid to obtain ferrites 8-14.

[0096] Embodiment 15

[0097] The difference from Example 2 is that the dispersant includes 1.5 kg of dispersion carrier 1 and 1 kg of dispersion aid 1 to prepare ferrite 15.

[0098] Example 16

[0099] The difference from Example 2 is that the dispersant includes 1.5 kg of dispersion carrier 1 and 1 kg of dispersion aid 2 to prepare ferrite 16.

[0100] Embodiment 17

[0101] The difference from Example 2 is that the dispersant includes 1.5 kg of dispersion carrier 1 and 1 kg of dispersion aid 3 to prepare ferrite 17.

[0102] Examples 18-20

[0103] The difference from Example 2 is that the dispersants respectively include dispersion carriers 1-3 added with a binder to obtain ferrites 18-20.

[0104] Examples 21-24

[0105] The difference from Example 2 is that additives 2-5 are used to replace additive 1 in Example 2 to obtain ferrites 21-24.

[0106] Comparative Example

[0107] Comparative Example 1

[0108] The difference between this comparative example and Example 2 is that the ferrite 27 is prepared without adding a dispersant.

[0109] Comparative Example 2

[0110] The difference between this comparative example and Example 2 is that the ferrite 28 is prepared without adding any additives.

[0111] Performance testing

[0112] (1) Magnetic property test: Use a magnetometer to test the coercive force and saturation magnetization of ferrite.

[0113] (2) Test of electrical properties: The ferrite was pressed into sheets and polished, and then silver electrodes were coated on both sides of the ferrite sheets. The sheets were fired at 400°C for 20 minutes, and the dielectric constant was tested using a tester. Ferrites 1-28 were tested, and the test results are shown in the following table.

[0114] Table 7 Performance test table

[0115]

[0116] Combining the performance test comparison in Table 7, we can find that:

[0117] (1) Combining Examples 1-3 and Comparative Examples 1-2, it can be found that by adjusting the ratio of the components in the ferrite and adjusting the content of the zinc source in the ferrite, the shape and size of the ferrite can be effectively controlled, and the possibility of agglomeration between the components of the ferrite can be reduced, so that the ferrite can obtain more uniform electromagnetic properties. Combining Table 7, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrite prepared in Example 3 are better, which shows that the ratio of the components in Example 3 is more appropriate.

[0118] (2) By comparing Example 2 with Examples 4-7, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrite prepared in Examples 4-7 are improved. This shows that the combination of mordenite and nano-spinel or mordenite and mesoporous silica summarized in this application can effectively increase the bonding performance between ferrite and dispersed carrier, and stably reduce the possibility of agglomeration between the components in ferrite.

[0119] (3) By comparing Examples 8-10, 11-12 and 13-14, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrites prepared in Examples 8-14 are improved, which shows that the modified auxiliary agent used in the present application to modify the dispersion carrier can construct a conductive network on the dispersion carrier, and the dispersion carrier forms an ordered six-hole structure, further improving the packaging and loading effect of the dispersion carrier on the ferrite powder, so that the ferrite obtains more uniform electromagnetic properties. Combining Table 7, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrites prepared in Examples 9, 11 and 13 are the best, which shows that the matching between the components in the modification treatment in Example 9 is more appropriate, the materials of the components in the modification auxiliary agent in Example 11 are more suitable, and the modification conditions in Example 13 are more appropriate.

[0120] (4) By comparing Examples 15-17 with Example 2, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrites prepared in Examples 15-17 are improved. This shows that the addition of a dispersing agent to the modifying agent in the present application can further reduce the possibility of agglomeration between the dispersed carriers through surface modification, so that the various components of the ferrite are evenly dispersed, thereby improving the uniformity of the ferrite performance. Combined with Table 7, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrite prepared in Example 16 are better, which shows that the matching between the various components in Example 16 is more appropriate.

[0121] (5) In combination with Examples 18-20, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrite prepared in Examples 18-20 are improved, which indicates that the present application adopts the method of adding a binding agent after the modification treatment to further increase the binding performance between the dispersed carrier and the ferrite powder, that is, to reduce the possibility of ferrite powder agglomeration. In combination with Table 7, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrite prepared in Example 19 are better, which indicates that the matching between the components of the binding agent in Example 19 is more appropriate.

[0122] (6) By comparing Examples 21-24 with Example 2, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrites prepared in Examples 21-24 are improved, which means that in the present application, additives are added to the ferrite, the additives dope the ferrite, adjust the shape and size of the ferrite powder, and improve the electromagnetic properties of the ferrite. In combination with Table 7, it can be found that the coercive force, saturation magnetization and dielectric constant of the ferrite prepared in Example 24 are better, which means that the ratio between the components of the additives in Example 24 is more appropriate.

[0123] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A nickel-zinc soft ferrite, characterized in that: The method comprises the following raw materials in parts by weight: 25-35 parts of an iron source, 3.5-9.5 parts of a nickel source, 4-10 parts of a zinc source, 10-20 parts of ammonia monohydrate, 20-30 parts of water, 1-2 parts of an additive and 2-3 parts of a dispersant, wherein the dispersant comprises a dispersing carrier having a layered structure, and the dispersing carrier comprises mordenite; The dispersed carrier further comprises any one of nano spinel and mesoporous silica, and the mass ratio of mordenite: nano spinel: mesoporous silica is 2-3:1-2:1-2; The dispersion carrier is a dispersion carrier modified by a modification agent, wherein the modification agent includes polyaniline, graphite and polyacrylamide, and the mass ratio of the polyaniline, graphite and polyacrylamide is 1-2:1-2:1-3; The modification treatment comprises the following steps: respectively weighing 6-8 parts of a dispersion carrier, 2-5 parts of sodium hydroxide, 20-30 parts of water, 10-15 parts of hexadecyltrimethylammonium bromide and 1-3 parts of a modification aid; stirring and mixing the dispersion carrier and the sodium hydroxide, and then calcining the mixture to obtain a mixture; stirring and mixing the mixture with water, leaching, and taking the upper layer liquid as a leaching liquid; stirring and mixing the leaching liquid, hexadecyltrimethylammonium bromide and the modification aid, and continuously stirring to obtain a mixed liquid; taking the mixed liquid for crystallization reaction, and then calcining the mixture to obtain a dispersion carrier modified with the modification aid; The additive includes one or more of niobium pentoxide, molybdenum oxide and tin oxide.

2. A nickel-zinc soft ferrite according to claim 1, characterized in that: The concentration of hexadecyltrimethylammonium bromide in the modification treatment is 3-5 g / L, the pH of the mixed solution is adjusted to 10-11, the crystallization temperature in the crystallization reaction is 90-110° C., and the crystallization time is 50-70 h.

3. A nickel-zinc soft ferrite according to claim 1, characterized in that: The modification treatment also includes the following steps: adding a bonding aid to the mixed solution, wherein the bonding aid includes silica gel and epoxy resin in a mass ratio of 3-5:1-2.

4. A nickel-zinc soft ferrite according to claim 1, characterized in that: The dispersant further comprises a dispersing aid, and the dispersing aid comprises any one of polyvinyl alcohol, zinc stearate and triethanolamine.

5. The method for preparing a nickel-zinc soft ferrite according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: S1. Mixing raw materials: stirring and mixing an iron source, a zinc source and a nickel source to obtain a mixed material, stirring and mixing the mixed material, water, ammonia monohydrate, an additive and a dispersant, and continuously stirring to obtain an intermediate solution; S2. Preparation of soft magnetic ferrite: subjecting the intermediate solution to a crystallization reaction to obtain a crystallized product. The crystallized product is filtered, a precipitate is retained, washed, dried, sintered, and cooled to obtain ferrite.

6. The method for preparing a nickel-zinc soft ferrite according to claim 5, characterized in that: The temperature of the sintering process in S2 is 400-500°C.

Citation Information

Patent Citations

  • Soft magnetic nickel and zinc ferrite nanometer powder and method for preparing same

    CN105753057A

  • Magnetic materials and products made therefrom

    US5322641A